Kajian Pemanfaatan Katuk (Sauropus Androgynus) sebagai Tanaman Herbal di RW 08 Desa Sindangsari Kecamatan Leuwigoong Kabupaten Garut - Awaludin Firdaus; Assyira Gapuraning Rahayu; Tri Cahyanto (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
The katuk plant (Sauropus androgynus) is a herbal plant that has many health benefits. Sauropus androgynus is one of the species of herbal plants that is widely known and spread in various countries, especially the Asian region, including Indonesia. This study aims to investigate the use of katuk leaf plant as an herbal medicine in RW 08 Sindangsari Village, Garut Regency through an ethnobotanical approach and to find out some of the benefits of katuk used as an alternative medicine. Data was taken by purposive sampling and continued with random sampling using electronic media. In data analysis, quantitative and qualitative approaches are used, including calculating Use Values (UV) and Fidelity Level (FL). The results of the study showed that the katuk plant had the highest UV value of 0.87 and FL 66.67% as a breast milk promoter, followed by other benefits, namely as a fever medicine, internal heat, cough medicine and so on. The results of the study showed that the katuk plant had the highest UV value of 0.87 and FL 66.67% as a breast milk promoter, followed by other benefits, namely as a fever medicine, internal heat, cough medicine and so on. The results show that katuk is a crucial plant in traditional medicine used by the residents of RW 08 Sindangsari Village.